Association between 2D landing biomechanics, isokinetic muscle strength and asymmetry in females using novel, task specific metrics based on ACL injury mechanisms. - Chelsea Oxendale; Grace Smith (PLoS ONE)
This study investigated the relationship between isokinetic muscle strength metrics, landing biomechanics, and their asymmetries, in females. Twenty-three female team sport athletes completed unilateral forward drop landings, and isokinetic muscle strength assessment of the knee extensors and flexors, on both limbs. Discrete two-dimensional kinematics of the trunk, hip, knee, and ankle in the sagittal and frontal plane and peak GRF were recorded during the drop landings. Novel, task-specific isokinetic strength metrics related to the landing task, such as peak concentric and eccentric torque, angle specific torque (AST), functional range and traditional/functional ratios were quantified. Asymmetry for kinematic and muscle strength data were quantified based on the individual variability of the task and the population mean and smallest worthwhile change. Functional concentric flexor range explained 15-18% of the variance in peak frontal trunk (P = 0.003) and hip motion (P = 0.007) and 22% in peak frontal knee motion (P = 0.005), when combined with the functional flexion ratio. Peak eccentric extensor torque explained 13-14% of the variance in peak sagittal hip (P = 0.014) and knee (P = 0.009) motion. Asymmetry in concentric extensor AST explained 28% of the variance in peak knee frontal plane asymmetry (P = 0.010), however the direction of asymmetry was rarely present on the same side for kinematic and strength variables. Novel and task specific isokinetic strength metrics explained small but significant variances in sagittal and frontal plane landing kinematics and asymmetry, which have previously been related to ACL injury risk.